Using micro pillar array columns (μPAC) for the analysis of permethylated glycans. Issue 13 (15th June 2021) - Cho, Byeong Gwan; Jiang, Peilin; Goli, Mona; Gautam, Sakshi; Mechref, Yehia
Abstract : The use of both 50 cm and 200 cm micro pillar array column (μPAC) for the analysis of permethylated glycan is demonstrated and assessed. Abstract : Glycosylation is a complex and common post-translational modification of proteins. To study glycosylation, liquid chromatography-mass spectrometry (LC-MS) is often used to profile and structurally characterize the glycans in biological systems. While bed packed reverse phase columns are frequently utilized for the separation of permethylated glycans, the use of newly commercialized micro array pillar nanoLC columns (μPAC) have not been demonstrated previously. Owing to its advantages such as low back pressure, reproducibility, and durability, we have investigated the viability of the μPAC for the analysis of permethylated glycans. In this work, we demonstrate the online purification ability of μPAC trapping column compared against PepMap trapping column. We also found that the 50 cm μPAC can be used for the analysis of both permethylated N - and O -glycans. The use of 50 cm μPAC was compared against the previous method. The use of 200 cm μPAC was also investigated for the permethylated glycan analysis. 200 cm μPAC demonstrated efficient separation of oligomannose glycan isomers as well as other complex glycans.